Yahoo奇摩 網頁搜尋

  1. ...0.707107*2 = 1.414(cor. to 4 sig. fig.) Simplify the following expressions . 4. √7+√28-√63 A. √7+√28-√63 = √7+√(2^2*7)-√(3^2*7) = √7...

  2. Simplify the following expression . 1. (3x2+x-2)/(x2-1) Sol: (3x2+x-2)/(x2-1) = [(3x-2)(x+1)]/[(x-1)(x...

  3. ... te following starements by using algebraic expressions . (a) 8more than 3 times of [k] (a) 3k+8 (b) Multiply the sum...

  4. WTF may stand for: "What the *****?", a common expression of confusion or bewilderment (also see Internet slang) Waking the ...

  5. Easy La. 3x-3(y+5x-25y) =3x-3y-15x+75y =-12x+72y I'm not really sure~.~.~, but it must be right!!!

  6. ...意見而已,如有錯誤請多多指教! 1.Find the units digit of the expression 1x2x3...x2009x2010. 條問題問咩,點計,答案 Sol: 條問題係問你呢條算式...

  7. 早睡 打齊用具:計數機、量角器、圓規 放鬆心情 處理 algebraic expression 時,人地叫你 expand 就唔好 factorize 處理 change of subject 時,將主項 (subject...

  8. ...右加 up ,down 改y 上加下減 Operations of algebraic expression : 同底指數可相加減,減完是負數的話,要整個變分子,唔要負號 同類項eg 5x...

  9. ... Association 2007 Annual Report of the freedom of expression in Hong Kong, referring to the government after the handover of...

  10. (a+b)^2-4(a-b)^2 =(a+b)^2-[2(a-b)]^2 ={(a+b)-[2(a-b)]}{(a+b)+[2(a-b)]} =(3b-a)(3a-b)